The Effects of Glacial Cover on Riverine Silicon Isotope Compositions in Chilean Patagonia - Pryer, Helena V.; Hatton, Jade E.; Wadham, Jemma L.; Hawkings, Jon R.; Robinson, Laura F.; Kellerman, Anne M.; Marshall, Matthew G.; Urra, Alejandra; Covey, Anna; Daneri, Giovanni; Häussermann, Vreni; Hendry, Katharine R. (Frontiers in Earth Science, 2020)
Proglacial rivers have been shown to have distinctive silicon (Si) isotope compositions, providing new insights into the mechanisms controlling Si cycling in the subglacial environment and suggesting terrestrial Si isotope exports may have varied between glacial and interglacial periods. However, Si isotope data are currently limited to a small number of glacial systems in the northern hemisphere, and it is unclear how compositions might vary across a spectrum of glacial influence. Using Chilean Patagonia as a unique natural laboratory, we present Si isotope compositions of 0.45 µm filtered (fSi), 0.02 µm filtered (DSi) and reactive amorphous (ASi) fractions from 40 river catchments with variable glacial cover and explore the key controls on Si cycling. The 0.45 µm filtered glacier-fed river samples displayed isotopically light compositions and a positive linear correlation with upstream glacial cover. This relationship was controlled by the inclusion of an isotopically light colloidal-nanoparticulate (0.02 -- 0.45 µm) silicate phase that was only present in glacier-fed rivers and dominated Si budgets in these catchments. This phase was predominately composed of feldspars and its lability in seawater is uncertain, representing a significant unknown in resolving glacial Si isotope exports from this region. When the colloidal-nanoparticulates were removed from solution by ultra-filtration, the resultant DSi isotope compositions of glacier-fed catchments were not isotopically distinct from some non-glacial rivers and exhibited no clear relationship with glacial cover. The colloidal-nanoparticulate concentration of other weathering-sensitive elements (Li, Mg, Ba, Sr) also showed a linear relationship with glacial cover, suggesting that their isotopic compositions could be affected in a similar manner. These findings highlight the benefit of size-fractionated sampling and the need for more research to understand the lability of colloidal-nanoparticulate species, especially in glacier-fed rivers. Finally, we explore the controls on river ASi isotope compositions and show how including these reactive particulate phases is critical to quantifying terrestrial Si isotope budgets, both in Patagonia and other global regions.